Imine Reductase‐Catalyzed Enantioselective Reduction of Bulky α, β‐Unsaturated Imines en Route to a Pharmaceutically Important Morphinan Skeleton. Issue 3 (7th December 2018) - Yao, Peiyuan; Xu, Zefei; Yu, Shanshan; Wu, Qiaqing; Zhu, Dunming
Abstract: The morphinan skeleton is an important sub‐structure in many medicines such as dextromethorphan, and can be constructed from 1‐benzyl‐1, 2, 3, 4, 5, 6, 7, 8‐octahydroisoquinoline (1‐benzyl‐OHIQ) derivatives. 1‐Benzyl‐3, 4, 5, 6, 7, 8‐hexahydroisoquinolines (1‐benzyl‐HHIQs), the precursors of 1‐benzyl‐OHIQs, constitute a type of bulky α, β‐unsaturated imines. Until now, the application of imine reductases (IREDs) to α, β‐unsaturated imines has only rarely been reported. In this study, through evaluation of 48 IREDs, both enantiomers of 1‐(4‐methoxybenzyl)‐1, 2, 3, 4, 5, 6, 7, 8‐octahydroisoquinoline (1‐(4‐methoxybenzyl)‐OHIQ) were obtained in high yield and excellent optical purity. Among the enzymes, the most steric hindrance‐tolerant IRED from Sandarearacinus amylolyticus (IR40) was able to convert various phenyl substituted 1‐benzyl‐HHIQ to the corresponding 1‐benzyl‐OHIQ derivatives with excellent enantiometric excess. These results provide an effective route to synthesize these important compounds via enantioselective reduction of bulky α, β‐unsaturated imine precursors, which can be readily prepared from 2‐(1‐cyclohexenyl)ethylamine and corresponding aryl acetic acids. Abstract :